Monetary policy rules: model uncertainty meets design limits - Alexander Dück; Fabio Verona (Bank of Finland, 2023)
Optimal monetary policy studies typically rely on a single structural model and identification of model-specific rules that minimize the unconditional volatilities of inflation and real activity. In our proposed approach, we take a large set of structural models and look for the model-robust rules that minimize the volatilities at those frequencies that policymakers are most interested in stabilizing. Compared to the status quo approach, our results suggest that policymakers should be more restrained in their inflation responses when their aim is to stabilize inflation and output growth at specific frequencies. Additional caution is called for due to model uncertainty.
Keywords: C49; E32; E37; E52; E58; 330; monetary policy rules; policy evaluation; model comparison; model uncertainty; frequency domain; design limits; DSGE models